Report of AAPM Task Group 235 Radiochromic Film Dosimetry: An Update to TG‐55. Issue 12 (30th October 2020) - Niroomand‐Rad, Azam; Chiu‐Tsao, Sou‐Tung; Grams, Michael P.; Lewis, David F.; Soares, Christopher G.; Van Battum, Leo J.; Das, Indra J.; Trichter, Samuel; Kissick, Michael W.; Massillon‐JL, Guerda; Alvarez, Paola E.; Chan, Maria F.
Abstract : The use of radiochromic film (RCF) dosimetry in radiation therapy is extensive due to its high level of achievable accuracy for a wide range of dose values and its suitability under a variety of measurement conditions. However, since the publication of the 1998 AAPM Task Group 55, Report No. 63 on RCF dosimetry, the chemistry, composition, and readout systems for RCFs have evolved steadily. There are several challenges in using the new RCFs, readout systems and validation of the results depending on their applications. Accurate RCF dosimetry requires understanding of RCF selection, handling and calibration methods, calibration curves, dose conversion methods, correction methodologies as well as selection, operation and quality assurance (QA) programs of the readout systems. Acquiring this level of knowledge is not straight forward, even for some experienced users. This Task Group report addresses these issues and provides a basic understanding of available RCF models, dosimetric characteristics and properties, advantages and limitations, configurations, and overall elemental compositions of the RCFs that have changed over the past 20 yr. In addition, this report provides specific guidelines for data processing and analysis schemes and correction methodologies for clinical applications in radiation therapy.